Effect of vitrification techniques on post-thaw survivability and in vitro maturation of immature bovine oocytes - B SAIKIA; P M BARUA; D DUTTA; B C DEKA; M DUTTA CHOUDHURY; H DEV; S HANDIQUE (Indian Journal of Animal Sciences, 2016)
The present study was conducted to evaluate the effectiveness of single-step and two-step vitrification techniques on post-thaw survivability and subsequent in vitro maturation of immature bovine oocytes. In two-step vitrification method, oocytes were first equilibrated in vitrification solution-I and then vitrification solution–II of 3.5M or 4.0M and 7.0M or 8.0M glycerol + ethylene glycol (GLY+EG) cryoprotectant respectively. In single-step vitrification technique oocytes were directly exposed to final vitrification solution (7 M or 8 M of GLY+EG) for 45, 60 and 75 sec to find out the suitable exposure time based on post-thaw survivability and subsequent development in vitro. In single step vitrification the per cent morphologically normal oocyte, cumulus cells expansion and polar body formation was found to be significantly highest in oocytes of least exposure (45 seconds) period for 8M of GLY+EG. The per cent recovery of morphologically normal oocytes was found to be higher in two steps (91.81±1.42 and 91.18±1.17) than single step vitrification technique (87.94±3.49 and 85.72±2.24 of 45 sec exposure time) for both 7M and 8M of GLY+EG. The rate of cumulus cells expansion and polar body formation was significantly higher in two-steps (81.34±2.65% and 76.54±3.60% and 56.93±1.52% and 51.76±2.87%) than single step vitrification technique (57.33±3.90% and 56.91±4.66% and 33.17±5.34% and 32.70±2.91%). From the study it was concluded that two-step vitrification technique was more effective on post-thaw survivability and subsequent in vitro maturation of immature bovine oocytes.